Analysis of Detergent Waste Absorption Using Water Spinach (Ipomoea aquatica) - Syarifa Wahidah Al Idrus; R. Rahmawati; Saprizal Hadisaputra; Hilman Qudratuddarsi (Pascasarjana, Mataram University, 2021)
This study aims to determine the absorption of water detergent waste using water spinach (ipomoea aquatica). This experimental study used a randomized block design. Water samples were planted with water plants according to the research design. Detergent concentrations were observed using the MBAS (Methylene Blue Active Substance) method. The results showed that water spinach was able to reduce the detergent concentration and improve the concentration of water quality parameters (DO, BOD, and COD). After the treatment of water kangkong, the ability to absorb detergent was seen with a decrease in detergent levels until day 28 of 54.17%. The highest detergent absorption on days 7 and 14.